Forelimb Amputation and Long-Term Follow-Up in a Female Donkey - Lopes Câmara, Antônio Carlos; Moreira, Igor Louzada; Caraldo, Eraldo Barbosa (Acta Scientiae Veterinariae, 2019)
Background: Limb amputation may be a life-saving procedure for animals and minimally impact their comfort and quality of life, as previously reported in pets. This procedure is an appropriate alternative to euthanasia when catastrophic injury to a limb prevents its successful restoration. In horses, limb amputation has been performed for the past 40 years. Although in the reviewed literature there are no scientific reports of limb amputation in donkeys. This paper aimed to report a successful forelimb amputation and long-term follow-up in a female donkey. Case: A 10-month-old and 95 kg female Nordestino donkey was evaluated for a wound with bone exposition on the left forelimb. Physical examination revealed that the donkey was alert with moderate body condition score, tachycardia, tachypnea, and a medial wound revealing the necrotic aspect of the left radius. Radiographic examination presented Salter-Harris type 1 exposed radius fracture. Hematology revealed normocytic and normochromic anemia, and hyperfibrinogenemia. Due to the catastrophic injury and no forecast for building a prosthesis, the donkey underwent general anesthesia for left forelimb amputation through the midhumerus diaphysis. A fish-mouth skin incision was performed on the midhumerus, the underlying musculature was dissected and the vessels ligated until the bone could be accessed. Then, a sterile saw wire was used to transect it, and bone edges were rounded. Muscle and fascia were harvested with the skin to provide additional padding at the end of the stump. Postoperatively, the donkey was submitted to broad spectrum antibiotic, anti-inflammatory and analgesic therapy, and tetanus prophylaxis. Preventative treatment for overload laminitis included frog support pads and resting leagues on all three legs. No short-term complications were observed and the donkey made a full recovery. Long-term complications included fistula formation on the stump, and distal interphalangeal joint hyperflexion, probably by weight overload causing acquired deep digital tendon contracture on the right forelimb. Currently, eight years (96-months) past surgery, the donkey is still well adapted and has a good quality of life even without a limb prosthesis. Discussion: Traditionally, catastrophic leg injury in equids often requires euthanasia. Currently, limb amputation is becoming more accepted by owners and a viable life salvage option. In horses, limb amputation by disarticulation using a caudal flap technique is the most usual surgical technique, but presents some chronic complications, such as osteomyelitis of the stump, pressure sores from the prosthesis and contralateral limb failure. Although not commonly performed in equids, limb amputation through the midhumerus diaphysis was well accepted by the donkey. In horses, survival rate reached 50% and 32.5% at 18 and 24 months after amputation with prosthetic fitting, respectively. The donkey herein reported is still alive and presenting a good life quality at 96-months post-surgery, even without a forelimb prosthesis. This kind of feature has been only reported in a Samba deer followed-up for 10-months, showing good corporal condition, walking and even running at slow speed, using three legs. To the authors knowledge this is the first scientific report of limb amputation in a donkey. We emphasize that documenting more limb amputation in equids is essential to obtain conclusions about the prognosis, life expectancy and expected quality of life.